Idâratu Tandzhîm Barnâmij al-Mukatstsaf fî Waqti Tsalâtsati Asyhur li Ta'allumi al-Lughah al-'Arabiyah bi Ma'had al-Nûr bi Pakis Magelang - Setiawan, Andi; Mawardin, Mawardin; Arifa, Zakiya (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2020)
The coordination of organization management in an institution had an important influence on the institution itself. But there were some cases still be found that related to an institution had not ideal organization management well. As my research did, I do in an institution that had not ideal organization management as well as should be. As one of the cased that was about a manager as the leader in the institution was still not had an organizational structure as clear yet. The manager only gave the oral division of duty to each member without made an organizational structure outline for them so it was made the position among leaders and members could not see. To analyze this cased The Researcher used a qualitative research approach with descriptive methods through interview and documentation techniques. This study discussed: 1) Management of organizing, 2) Problems in organizing at Islamic boarding schools in An-Nur Pakis Magelang.